On asymptotic normality of estimates for correlation functions of stationary Gaussian processes in the space of continuous functions - Buldygin, V. V.; Zayats, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We establish conditions of the weak convergence of the empirical correlogram of a stationary Gaussian process to some Gaussian process in the space of continuous functions. We prove that such a convergence holds for a broad class of stationary Gaussian processes with square integrable spectral density.